2017
DOI: 10.1002/bies.201700066
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the twilight of death

Abstract: After a vertebrate dies, many of its organ systems, tissues, and cells remain functional while its body no longer works as a whole. We define this state as the "twilight of death" - the transition from a living body to a decomposed corpse. We claim that the study of the twilight of death is important to ethical, legal and medical science. We examined gene expression at the twilight of death in the zebrafish and mouse reaching the conclusion that apparently thousands of transcripts significantly increase in abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Third, death can be seen as a condition of extreme stress [ 2 ]. Hence, the increased abundance of specific transcripts shortly after death could be attributed to genes encoding proteins involved in resilient pathways (e.g., heat shock, Hsp , hypoxia-related, Hif1ab and oxidative stress, Gadd45a , March4 ) to compensate for extreme stress and increase survival chances [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, death can be seen as a condition of extreme stress [ 2 ]. Hence, the increased abundance of specific transcripts shortly after death could be attributed to genes encoding proteins involved in resilient pathways (e.g., heat shock, Hsp , hypoxia-related, Hif1ab and oxidative stress, Gadd45a , March4 ) to compensate for extreme stress and increase survival chances [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet to date, such studies have not been officially used to assess organ quality and/or transplantation success. Therefore, Pozhitkov and Noble [ 2 ] have suggested a closer examination of the relationship between gene expression and postmortem time which might yield valuable information about organ quality. Thus, activation of many developmental genes, including Mdga2 , Ripply3 , or tumor suppressor Tnfrsf9 , and the oncogenic ( Tpr , Csnk2a1 ) transcripts in the first 24 h after death [ 1 ] may increase the risk of carcinogenesis in the transplanted organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death is the cessation of biological functions that maintain homeostasis and sustain a living organism [ 54 ]. The death of an animal means that its systems, organs, tissues, and cells stop functioning as a whole, which implies that the individual parts may still be alive at the time when the body dies [ 54 ].…”
Section: The Aging Of the Circadian Clock In Drosophila mentioning
confidence: 99%
“…The investigation of post-mortem RNA dynamics can provide novel insights into the biology of death. Previous studies have suggested that there is some level of active post-mortem mRNA transcription 1 4 . Although most of the transcriptome is shutting down or degrading, approximately 1% of the brain transcriptome is turned on in response to death 2 .…”
Section: Introductionmentioning
confidence: 99%